2023
DOI: 10.3389/fevo.2023.988126
|View full text |Cite
|
Sign up to set email alerts
|

Integrating traditional ecological knowledge into US public land management: Knowledge gaps and research priorities

Abstract: Traditional Ecological Knowledge (TEK) is an understanding of natural systems acquired through long-term human interactions with particular landscapes. Traditional knowledge systems complement western scientific disciplines by providing a holistic assessment of ecosystem dynamics and extending the time horizon of ecological observations. Integration of TEK into land management is a key priority of numerous groups, including the United Nations and US public land management agencies; however, TEK principles have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 304 publications
(483 reference statements)
0
2
0
Order By: Relevance
“…In the most successful manager–researcher partnerships, scientists collaborate with land managers at the initial stage of developing research questions that are relevant for revegetation and maintain active collaboration throughout the research process (Rohal et al 2018; Funk et al 2020). In addition to partnerships with research institutions and plant material vendors, research has also shown that including local and indigenous ecological knowledge in management can improve monitoring efficiency and restoration outcomes (Souther et al 2023). While the present study focused on land managed by state and federal entities, the perspectives of tribal and privately managed lands are important for a full understanding of wetland revegetation in the Intermountain West.…”
Section: Discussionmentioning
confidence: 99%
“…In the most successful manager–researcher partnerships, scientists collaborate with land managers at the initial stage of developing research questions that are relevant for revegetation and maintain active collaboration throughout the research process (Rohal et al 2018; Funk et al 2020). In addition to partnerships with research institutions and plant material vendors, research has also shown that including local and indigenous ecological knowledge in management can improve monitoring efficiency and restoration outcomes (Souther et al 2023). While the present study focused on land managed by state and federal entities, the perspectives of tribal and privately managed lands are important for a full understanding of wetland revegetation in the Intermountain West.…”
Section: Discussionmentioning
confidence: 99%
“…The discipline, as a result, experienced a substantial shift in the recognition of Indigenized research studies, which present mutual forms of dialogue, research, theory, and action (Kovach 2016, Ramos 2022 Schley et al 2022). This is a testament to the adoption of TEK, with recent publications indicating a statistically significant increase in TEK literature over the same time period (Jessen et al 2022, Souther et al 2023. Additionally, Indigenous research methodologies (Chalmers 2017, Smith 2021 have gained traction as a potential course of action (Ramos 2018) in which TEK and research in wildlife management is more appropriately conducted with, rather than on, Indigenous communities (Lavallée 2009).…”
Section: Recognitionmentioning
confidence: 99%
“…The United Nations Declaration on the Rights of Indigenous Peoples established a universal framework to uphold the rights and interests of Indigenous people including their role in management and governance of land and sea Country. Governments and researchers are increasingly creating spaces for Indigenous roles and perspectives to improve our collective understanding and management of natural resources (Nakashima et al 2018 ; Souther et al 2023 ). Key to the success of these efforts are genuine two-way partnerships between Indigenous peoples and science organisations that move beyond knowledge inequities to fully integrate traditional and contemporary knowledge in a way that equally shares their power and participation (Hill et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Healthy Country Plans outline key targets for conservation and set out strategies to abate threats, restore targets, and evaluate their ongoing health and impacts through performance indicators. Science partnerships are essential elements of management plans in IPAs; they can provide training and assist in the collection of systematic monitoring data to inform, implement and evaluate management actions (Depczynski et al 2019 ; Rist et al 2019 ; Souther et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%